Call for Papers - Undressing the Bawdy - Editors, The (Pivot: A Journal of Interdisciplinary Studies and Thought, 2011)
Undressing the Bawdy Call for Papers for the Second Issue of Pivot: A Journal of Interdisciplinary Studies and Thought, published by the Graduate Program in English at York University